The impact of thin-capitalization rules on multinationals' financing and investment decisions - Thiess Büttner; Michael Overesch; Ulrich Schreiber; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper analyzes the role of Thin-Capitalization rules for capital structure choice and investment decisions of multinationals. A theoretical analysis shows that the imposition of such rules tends to affect not only the leverage and the level of investment but also their taxsensitivity. An empirical investigation of leverage and investment reported for affiliates of German multinationals in 24 countries in the period between 1996 and 2004 offers some support for the theoretical predictions. While Thin-Capitalization rules are found to be effective in restricting debt finance, investment is found to be more sensitive to taxes if debt finance is restricted.
Keywords: H25; H26; G32; 330